Evaluation of the protein characteristics of four diverse grasses - Mathis, C.P.; Abdelgadir, I.E.O.; Cochran, R.C.; Heldt, J.S.; Woods, B.C.; Vanzant, E.S.; Olson, K. C.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forage protein characteristics in four grasses were evaluated by the nylon bag method. All of the forages used (Bermudagrass hay, brome hay, forage sorghum hay, and prairie hay) were of relatively low quality, except the Bermudagrass, which was of average quality. The forages differed in the size of different protein fractions and in the rate and extent of protein degradation. Predicted extent of ruminal protein degradation (i.e., ruminal protein availability) was lowest for prairie hay, intermediate for Bermudagrass and forage sorghum hay, and highest for the brome hay.
Keywords: Beef; Forage; In situ analysis; Protein; Degradable intake protein